Inherited variants in CHD3 show variable expressivity in Snijders Blok-Campeau syndrome - Coenen-Van der Spek, Jet; den Hoed, Joery; Snijders Blok, Lot; Dingemans, Alexander J. M.; Schijven, Dick; Nellaker, Christoffer; Venselaar, Hanka; Astuti, Galuh D. N.; Barakat, Tahsin Stefan; Bebin, E. Martina; Beck-Wödl, Stefanie; Beunders, Gea; et al. (Genetics in medicine, 2022)
Purpose - Common diagnostic next-generation sequencing strategies are not optimized to identify inherited variants in genes associated with dominant neurodevelopmental disorders as causal when the transmitting parent is clinically unaffected, leaving a significant number of cases with neurodevelopmental disorders undiagnosed. - Methods - We characterized 21 families with inherited heterozygous missense or protein-truncating variants in CHD3, a gene in which de novo variants cause Snijders Blok-Campeau syndrome. - Results - Computational facial and Human Phenotype Ontology-based comparisons showed that the phenotype of probands with inherited CHD3 variants overlaps with the phenotype previously associated with de novo CHD3 variants, whereas heterozygote parents are mildly or not affected, suggesting variable expressivity. In addition, similarly reduced expression levels of CHD3 protein in cells of an affected proband and of healthy family members with a CHD3 protein-truncating variant suggested that compensation of expression from the wild-type allele is unlikely to be an underlying mechanism. Notably, most inherited CHD3 variants were maternally transmitted. - Conclusion - Our results point to a significant role of inherited variation in Snijders Blok-Campeau syndrome, a finding that is critical for correct variant interpretation and genetic counseling and warrants further investigation toward understanding the broader contributions of such variation to the landscape of human disease.